2006
DOI: 10.4081/gh.2006.279
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the application of geographical information systems and remote sensing in veterinary parasitology

Abstract: IntroductionApplication of geographical information systems (GIS) and remote sensing (RS) in veterinary and human medical sciences, particularly in veterinary and human parasitology, is rapidly advancing. During the past 10-20 years the publication of original research articles and reviews in veterinary and human health with an emphasis on GIS and/or RS has followed an exponential trend (Hendrickx et al., 2004). In addition, recent GIS/RS symposia organized at national and international conferences, and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 57 publications
1
87
1
1
Order By: Relevance
“…Our study indicates that indoor relative humidity and temperature are highly associated with increased risk for P. argentipes breeding and leishmaniasis infection. Previous work reported that prediction of disease occurrence is based on climatic and/or environmental requirements of sandfly (Cringoli et al 2005, Rinaldi et al 2006. However, our results showed significant associations between vector abundance, indoor temperature and relative humidity, which might be a relevant predictor for disease prevalence.…”
Section: Discussioncontrasting
confidence: 56%
“…Our study indicates that indoor relative humidity and temperature are highly associated with increased risk for P. argentipes breeding and leishmaniasis infection. Previous work reported that prediction of disease occurrence is based on climatic and/or environmental requirements of sandfly (Cringoli et al 2005, Rinaldi et al 2006. However, our results showed significant associations between vector abundance, indoor temperature and relative humidity, which might be a relevant predictor for disease prevalence.…”
Section: Discussioncontrasting
confidence: 56%
“…Application of GIS and remote sensing (RS) in human and veterinary medical sciences, particularly in human and veterinary parasitology, is rapidly advancing (Yang et al 2005b;Hay et al, 2006;Rinaldi et al, 2006). GIS and RS are suitable tools for the creation of spatially-explicit databases, and the display of relevant data for health policy planning and discussion, guiding interventions and costeffective monitoring at a range of spatial scales (Tatem and Hay, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Geospatial tools, including geographical information systems (GIS) and satellite-based technologies such as remote sensing and global positioning systems (GPS), coupled with geostatistical approaches, are increasingly and successfully applied at different levels from sampling to risk profiling of parasitic diseases (Rinaldi et al, 2006;Brooker, 2007;Simoonga et al, 2009;Machault et al, 2011;Utzinger et al, 2011). Indeed, this represents an innovative and useful way to communicate finding to field researchers and decision-makers and it is a powerful approach that also addresses the spatial targeting of parasite control, including the choice of treatment to be applied.…”
Section: General Considerationsmentioning
confidence: 99%
“…The link with geospatial methodologies provides support that moves activities forward Chen et al, 2012). However, there is often a tendency to emphasise drug treatment and vaccines, while the importance of standardisation of geospatial strategies and diagnostics is neglected (Rinaldi et al, 2006;Bergquist et al, 2009;Solomon et al, 2012). It follows that further impetus for research on geospatial technology and links with more sensitive, standardised diagnostic techniques must take place.…”
Section: Introductionmentioning
confidence: 99%